Thai transgender women in Europe: Migration, gender and binational relationships. (March 2021) - Pravattiyagul, Jutathorn
The article identifies subtle structural and socio-political issues behind kathoeys ' (Thai male-to-female transgender) migration decisions and categorizes the structural aspirations of their migrations to Europe and their goals to be in binational relationships in their search for a "better life." The research was conducted in Thailand, Belgium, the Netherlands, the UK and Denmark. The article also reveals kathoeys ' irregular migration and outlines relevant literature in the light of gender, sexuality and migration, as well as their sentimental dynamic and feminine identity formation validated by their binational relationships under crypto-colonized cultural ideologies.